Will Academic Library Publishing Break OER? A Diffusion of Innovations Study. Issue 1 (13th December 2021) - Essmiller, Kathy; Asino, Tutaleni
Academic libraries are among the organizations advocating for open educational resources (OER), often playing a key campus role in education, advocacy, and support of their creation and publication. Publication of OER resonates with the role of the academic library. Because "incongruence in perceptions" (Chtena 2019: 24 ) can cause difficulties and unforeseen challenges with implementation and use of OER, organizations involved in OER initiatives need familiarity with how OER and organizational values align. The goal of this exploration was to investigate how academic libraries enact academic library publishing programs and the ramification that has in the diffusion process of OER in higher education. Data collected in this single case study research project was analyzed through the lens of Diffusion of Innovations Theory. The findings from the study suggest that, if academic libraries are to enact the creation and publication of OER in ways appropriate to their conception, those involved will need to be intentional about ensuring enactment of the values foundational to OER. Future suggested research includes a multiple-case study comparative research study looking at academic library publication of OER, exploration of how opinion leaders and attributes of innovations impact academic library publication of OER, and investigation into the impact of organizational structure on the diffusion of OER creation and publication.